ショウワキチ シュウヘン ノ ロガン チタイ ニ ソンザイ スル コショウ ノ イッパンテキ セイジョウ ニ ツイテ - 村山, 治太; ムラヤマ, ハルタ; MURAYAMA, Haruta (国立極地研究所, 1977)
P(論文) リュツォ・ホルム湾東岸の露岩地域に点在する湖沼群について,一般的性状と水質を知る目的で,スカーレン地区から日の出岬の間に存在する49の湖沼を調査した.湖面が結氷した9月から11月の間に,湖氷中央部に穴をあけ,氷厚,水深,水温を測定し,一部の塩湖では湖盆地形も観察した.表層および底層の2層に分けて採水し,pH,電気伝導度を昭和基地で測定したが,主成分や蒸発残留物などは帰国後分析を行った.測定の結果,昭和基地周辺の湖沼の塩分濃度は,塩化物イオソとして最低値1.3 mg/l,最大値210 g/l(比重1.223)の広範囲にまたがり,そのうち12は塩湖に相当する濃度であった.またこれらの塩湖は,地形的環境からみて海跡湖と思われるものが大部分である低 高塩分の由来については他の要因もあることが推定された. Limnological studies were carried out in the 1972 winter to know general characteristics of the Antarctic water system and geochemical feature of the Antarctic lakes located in the ice-free areas of the east coast of Lutzow-Holm Bay. The water samples were collected from September to November when the surface of the lakes was covered with the ice. The thickness of the lake ice, the depth of the lakes and the water temperature were measured on the spot. pH and electric-conductivity were measured at Syowa Station after melting the frozen water samples, but most of the chemical analysis was conducted at the laboratory of our Department after were carried back the samples in frozen state, employing general and conventional analytical methods. Chemical components of the lakes varied considerably, ranging from 1.3 mg/l to 210 g/l on the chloride ion concentration. Most of the high saline lakes in this area seems to be relict lakes. departmental bulletin paper